Establishment of an unfed strain of Paramecium bursaria and analysis of associated bacterial communities controlling its proliferation - Himi, Eiko; Miyoshi-Akiyama, Tohru; Matsushima, Yuri; Shiono, Iru; Aragane, Seiji; Hirano, Yui; Ikeda, Gaku; Kitaura, Yuki; Kobayashi, Kyohei; Konno, Daichi; Morohashi, Ayata; Noguchi, Yui; et al. (Frontiers in Microbiology, 2023)
The ciliate Paramecium bursaria harbors several hundred symbiotic algae in its cell and is widely used as an experimental model for studying symbiosis between eukaryotic cells. Currently, various types of bacteria and eukaryotic microorganisms are used as food for culturing P. bursaria; thus, the cultivation conditions are not uniform among researchers. To unify cultivation conditions, we established cloned, unfed strains that can be cultured using only sterile medium without exogenous food. The proliferation of these unfed strains was suppressed in the presence of antibiotics, suggesting that bacteria are required for the proliferation of the unfed strains. Indeed, several kinds of bacteria, such as Burkholderiales, Rhizobiales, Rhodospirillales, and Sphingomonadales, which are able to fix atmospheric nitrogen and/or degrade chemical pollutants, were detected in the unfed strains. The genetic background of the individually cloned, unfed strains were the same, but the proliferation curves of the individual P. bursaria strains were very diverse. Therefore, we selected multiple actively and poorly proliferating individual strains and compared the bacterial composition among the individual strains using 16S rDNA sequencing. The results showed that the bacterial composition among actively proliferating P. bursaria strains was highly homologous but different to poorly proliferating strains. Using unfed strains, the cultivation conditions applied in different laboratories can be unified, and symbiosis research on P. bursaria will make great progress.